Kemija: skripta - Lobnik, Aleksandra; Volkmajer Valh, Julija (University of Maribor Press, 2017)
Chemistry: script. Chemistry is natural science that studies the composition, structure and properties and change of matter. Chemistry (scriptum) includes topics such as atom, the properties of atoms, how atoms form chemical bonds to create chemical compounds and the interactions between substances through chemical reactions to form different substances. Chemistry is a highly multidisciplinary science and it bridges other natural and technical sciences. Chemistry is today divided into several different disciplines such as: inorganic chemistry, organic chemistry, biochemistry, physical chemistry and analytical chemistry. The fundamentals of organic chemistry are also presented in the Chemistry (scriptum).